Decision Making Pengambilan Keputusan dalam Melakukan Aborsi oleh Perempuan Usia 20-30 Tahun - Poespa Mayendri, Edelwis Tiara; Prihantoro, Edi (LPkM Universitas Bakrie, 2020)
Freedom in abortion has been packaged to cover up the real facts, meaning that few people know about the dangers of abortion, but places selling illegal abortion drugs can still flap their wings to sell in the world of online commerce. This dedication discusses the decision making in having an abortion by women aged 20-30 years. The crisis of knowledge about sexual education makes abortion perpetrators less aware of the dangers of abortion, meaning that the community does not really understand whether or not they can have an abortion. Abortion is done not only because of intention or desire. The process of making decisions about abortion perpetrators is also different, making decisions that make doubts when pregnant are difficult, lack of knowledge and falling into difficult choices make people do things that shouldn't be done, how is the process of making decisions about abortion perpetrators. Therefore, this study uses a dedication method and uses the theory of decision making as a knife of analysis in decision making in performing abortion by women aged 20-30 years. This case was taken considering that the rate of abortion in Indonesia is very high, and maternal mortality due to abortion is a concern. So that this service approach uses a phenomenological approach to determine the decision making in carrying out abortion by women aged 20-30 years. Phenomenology tries to identify a meaning behind the way the abortion perpetrator takes decisions, so that what is highlighted is the abortion perpetrator's decision-making process.